DEVELOPING EXTENSIVE READING MATERIAL FOR SEMESTER 2 STUDENTS OF YOGYAKARTA UNIVERSITY OF TECHNOLOGY - Sungkawati Kardi Wahyuningsih (Asosiasi Dosen Perguruan Tinggi Islam, 2018)
This research study was aimed at developing extensive reading material for semester 2 students of Yogyakarta University of Technology. This research was a Research and Development study that included the steps of needs analysis, course grid design, product development, product validation, product revision, try-out, and study of the final product. This research developed ten units of extensive reading material. The extensive reading material was developed according to the needs analysis data. The need of semester 2 students of Yogyakarta University of Technology is to improve their reading skills. The appropriate extensive reading material are describe the language skills clearly, look nice, give a lot practice, give feedback and let the learners know how to complete the tasks, give examples and tell the learners how to learn best. The needs-related appropriate extensive reading material in terms of their components are: the goal of learning reading is to improve the students’ reading skills; the input presents interesting pictures and vocabulary list; the procedure presents interesting and enjoyable activities; the learners’ role is as the active reader; the teacher’s role is the feedback giver; and the setting is individual work. The needs-related arrangement of the components of appropriate extensive reading material in terms of their organisations are arranged into three stages, namely: introduction, exercises, and evaluation